A hydrothermal seedling emergence model for Conyza bonariensis. (10th April 2013) - Zambrano‐Navea, C; Bastida, F; Gonzalez‐Andujar, J L
Summary: Conyza bonariensis is a South American native annual Asteraceae that has been introduced to the Mediterranean, where it behaves as a ruderal plant and a weed that is difficult to control in several crops. The development of predictive models can contribute to control measures at early growth stages, but currently there are no studies to predict seedling emergence of Conyza species. Our objectives were to develop and evaluate a model for predicting emergence response of C. bonariensis to the soil hydrothermal environment. A hydrothermal seed germination model was fitted to time course germination data from germination tests carried out at different constant temperatures and water potentials with the aim of establishing the hydrothermal parameters characterising C. bonariensis seed germination. The relationship between cumulative seedling emergence and cumulative hydrothermal time under field conditions was analysed using the Gompertz function. Model development was based on 2 years' data from a field experiment. Base temperature and base water potential for seed germination were estimated at 10.6°C and −0.70 ± 0.151 MPa, respectively. The emergence model showed a very good fit to the experimental data. According to this model, seedling emergence starts at 15 accumulated hydrothermal time (HTT) after sowing, and 50 and 95% emergence is completed at 53 HTT and 105 HTT, respectively. For model evaluation, independent field experiments were carried out in two localities. Cumulative seedling emergence was accurately predicted by the model. Results indicate that this model can be useful as a predictive tool contributing to effective control of C. bonariensis populations.